Objectively assessed physical activity, sedentary time and waist circumference among prostate cancer survivors: Findings from the National Health and Nutrition Examination Survey (2003-2006) - Lynch, B.; Dunstan, D.; Winkler, E.; Healy, Genevieve; Eakin, E.; Owen, N. (2011)
Physical activity is well-established on the cancer survivorship research agenda, but prostate cancer survivors remain an understudied population. Additionally, the unique relationships between sedentary time and health outcomes have not yet been considered in this group. We examined the associations of accelerometer-assessed physical activity and sedentary time with waist circumference in 103 prostate cancer survivors from the National Health and Nutrition Examination Survey 2003-2004 and 2005-2006. Participants wore an Actigraph accelerometer for 7 days, and activity levels were summarised as moderate-to-vigorous intensity activity (accelerometer counts/minute =1952), light-intensity activity (counts/minute 100-1951) and sedentary time (counts/minute < 100). Moderate-to-vigorous intensity physical activity was inversely associated with waist circumference (ß=-6.728, 95% CI: -12.267, -1.190, P= 0.020), equating to a top versus bottom quartile difference of 13.7cm. No discernable relationship existed between light-intensity activity or sedentary time and adiposity. This is the first study to objectively measure the activity levels of prostate cancer survivors. Increasing moderate-to-vigorous activity may assist this population with weight management. More research into the relationships of light-intensity physical activity and sedentary behaviour with health outcomes among prostate cancer survivors is warranted, given the strong relationships seen in the broader population. © 2010 Blackwell Publishing Ltd.